Workshop in a Box: Project Management for Faculty and Learner Development - Christian Burke; Tracy Fulton; Huiju Carrie Chen (Association of American Medical Colleges, 2011)
Abstract Introduction Faculty who serve as project advisors typically have a great deal of content expertise but may lack the experience and practical tools with which to manage these projects. This workshop was initially conceived as a faculty development workshop to help faculty new to advising scholarly projects work with student and resident collaborators. Methods This 2-hour session uses a series of large- and small-group discussions, accompanied by handouts, to explore the various phases of project management and discuss possible pitfalls. Results Over the past 3 years, we have successfully run this workshop in multiple local settings for groups ranging from 8 to 25 participants. Participants in this workshop have included college students, medical students, residents, fellows, and faculty. We have also run this workshop at a regional medical education meeting and a national pediatrics meeting. The workshop has been well-received; overall effectiveness ratings have ranged from 4.10 to 4.75 on a 5-point Likert scale (5 = best). Discussion The workshop can be used to provide instruction on project management to diverse audiences such as mentors, mentees, and those engaged in projects themselves. Ideally, this approach should provide a common language and set of tools for both advisors and advisees in order to increase the likelihood of project success. In addition, the materials provided can also be directly accessed by advisors and advisees who may wish to independently utilize the structural guidelines and information about project management.